Leptomischus multiflorus (Argostemmateae: Rubiaceae), a new species from southern Vietnam - Nuraliev, Maxim S.; Nguyen, Khang Sinh; Pham, Thoa Kim Thi; Nguyen, Cuong Huu; Quang, Bui Hong; Lyskov, Dmitry F.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Wu, Lei (Phytotaxa, 2022)
Leptomischus multiflorus, a new species of the tribe Argostemmateae (Rubiaceae), is described and illustrated. The species was discovered in 2022 in Quang Nam Province, southern Vietnam. The new species is characterized by rich indumentum on almost all plant parts, distylous flowers, and minutely puberulent ovary disk. Leptomischus multiflorus differs from all its congeners by the following features: leaf blades up to 23 cm long with up to 25 pairs of secondary veins, many-flowered inflorescences, and corolla tube 7–8 mm long and hairy outside. It additionally differs from the morphologically closest species, L. anisophyllus, in weakly anisophyllous to nearly isophyllous leaves, calyx lobes 2–2.5 mm long (about 1/3 length of corolla tube), corolla lobes with horn-like appendages, anthers 1–1.3 mm long, style hairy in distal half, pin flowers with filaments adnate at the middle of the corolla tube and with stigma lobes 1 mm long, and thrum flowers with style 2.5–3 mm long.